(untitled) (Al-Qamar, 2018)
This article studies the discovery of “Karbal Katha” in the perspective of its compiler. It explores that Mukhtaruddin Ahmed, while compiling the Karbal Katha, made its literary and linguistic features the subject of discussion. Criticism has also been provided for the use of proverbs, techniques and innovations in the structure of sentences. Karbal Katha is a literary work as well as a religious work, so it also contains many historical data, descriptions of historical events which are sometimes very short and sometimes based on length to determine the historical status of the text. At the end, the list of names and persons, list of books and places and other matters are given. Mukhtar-ud-Din Ahmed has compiled Dastan-e-Fazli with great care and diligence. Competent hard work and good order are in every way commendable and of paramount importance. Mukhtaruddin Ahmed also commented on the reflection of the cultural environment in Karbal Katha.